2008
DOI: 10.1007/s00213-008-1100-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of amphetamine sensitization is associated with recruitment of a reactive neuronal population in the nucleus accumbens core

Abstract: Rationale Repeated exposure to psychostimulant drugs causes a long-lasting increase in the psychomotor and reinforcing effects of these drugs and an array of neuroadaptations. One such alteration is a hypersensitivity of striatal activity such that a low dose of amphetamine in sensitized animals produces dorsal striatal activation patterns similar to acute treatment with a high dose of amphetamine. Objectives To extend previous findings of striatal hypersensitivity with behavioral observations and with cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 45 publications
4
41
0
Order By: Relevance
“…Both test dose and test time are important parameters for expression of AMP-induced stereotypy (Segal 1976). Under our experimental conditions, we did not note any AMP stereotypy, confirming the negative findings of others (Nordquist et al 2008). One must also consider whether tolerance to AMP contributed to the observed behaviors.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Both test dose and test time are important parameters for expression of AMP-induced stereotypy (Segal 1976). Under our experimental conditions, we did not note any AMP stereotypy, confirming the negative findings of others (Nordquist et al 2008). One must also consider whether tolerance to AMP contributed to the observed behaviors.…”
Section: Discussionsupporting
confidence: 90%
“…Amphetamine-induced locomotor activation has also been associated with enhanced DArgic activity (Ventura et al 2004;Nordquist et al 2008). Greater AMP-induced DArgic activation was noted in group-housed rats compared to socially isolated rats (Leng et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Although the CP has been implicated in the sensitization of both locomotor activity and stereotypy (Vanderschuren and Kalivas 2000;Vanderschuren et al 2002), sensitization-induced increases in Fos-IR are only occasionally observed in the CP (Vanderschuren et al 2002;Rademacher et al 2007;Mattson et al 2008;Nordquist et al 2008; for negative results, see Crombag et al 2002;Ostrander et al 2003;Hope et al 2006;Mattson et al 2007;Conversi et al 2008). Perhaps explaining this inconsistency, Mattson et al (2008) reported that "neuronal ensembles" in the CP and nucleus accumbens exhibit increased Fos-IR after cocaine challenge and this neuronal activity may be responsible for context-dependent locomotor sensitization.…”
Section: Discussionmentioning
confidence: 90%
“…For this reason, it is surprising that sensitized adult rats do not typically exhibit increased Fos-IR in the PFC (e.g., see Todtenkopf et al 2002;Conversi et al 2008;Nordquist et al 2008). Our finding of elevated Fos-IR in the PFC is consistent with the presumed importance of this structure for behavioral sensitization and may indicate that alterations in cortical Fos are easier to detect in young animals.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation